Kadar Glukosa Darah dan Gambaran Histopatologi Ginjal Tikus Diabetik yang Diberi Diet Tempe Kacang Gude (Cajanus cajan (L) Millsp) - Yusasrini, Ni Luh Ari; Duniaji, Agus Selamet (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 4 No 2 (2019), 2019)
The specific purpose of this study was to determine changes in blood glucose levels and histological features of diabetic rats that were given a diet of pigeon pea ( Cajanus cajan (L) Millsp) tempeh. The stages of the research included making the pigeon pea tempe, making standard and treatment feed and followed by bioassay testing using alloxan-induced diabetic rats. The analysis included proximate analysis, fiber and antioxidant capacity in raw materials, analysis of blood sugar, weight weighing and observation of kidney histopatological. The results of this study are expected to be beneficial for the development of pigeon pea as functional food, especially for the dietary therapy of patients with diabetes mellitus. The results showed that the feeding of pigeon pea tempeh showed hypoglycemic effect which was marked by a decrease in rat blood glucose levels from 323.68 mg / dL to 200.37 mg / dL. Observations on renal histology showed that the PS (-) and PTKG groups showed almost the same glomerular condition and fewer cells experienced necrosis compared to the PS (+) group.